(untitled) (Fiep Bulletin - online, 2014)
This study was aimed at verifying if there is difference among the values of perceptual of body fat (%BF) obtained by the methods anthropometric [through the techniques of skinfolds (A-SF+C) and circumferences - generalized equations (A-GC) and specific (A-SC)] and of hydrostatic weighing (HW). Physically active university students were assessed, divided into 2 groups: 23 men (MG) (age of 21,90±2,28, stature of 176,11±6,26cm, 73,98±8,54kg), 13 women (GF) (age of 20,92±1,70, stature of 162,47±3,61cm, 57,22±6,96kg). According to the results obtained all the values of %GC for the methods investigated differed statistically (HW vs A-GC p <0,05; HW vs A-SF+C, HW vs A-SC, A-SF+C vs A-GC, A-SF+C vs A-SC, A-GC vs A-SC p <0,01), when considering MG. In relation to FG the %BF became statistically different HW vs A-GC (p <0,05), HW vs A-SF+C (p <0,01) and HW vs A-SC (p <0,01) when the two methods were considered, however, when analyzed the anthropometric method it was observed that the valued results, considering the different techniques and/or equations, did not differ significantly among themselves. Concerning the obtained data and evaluated groups, it is conclued that the prediction of the %BF can be made from values of circumferences, being able to use specific or generalized equations when the evaluated public was composed of women. Considering the facility in the application of the technique of circumferences and in the obtaining of the results, the obtained information becames an useful tool for the professionals that make use of the assessment of body composition. In relation to the masculine public the obtained data were not conclusive being necessary further investigations.